Toshio Doko the determination for administrative reform [videorecording]. (Japan Keizai Koho Center, Japan Institute of Social and Economic Affairs)
Looks at Doko's administrative policy and office administrative reforms that aided in the development of the economic conditions of Japan.
VHS.
Keywords: Doko, Toshio -- 1896-1988.; Economic development -- Japan; Industrial management -- Japan; Japan -- Economic conditions; Japan -- Economic policy